Sovietisation of Schools in the 1940/41 School Year: bolshevis indoctrination,compain of eadult education in in Schools of Šakiai County; Teachers between Resistance, Conformism and Collaboration; Repressions (3) - Buchaveckas , Stanislovas (Genocidas ir rezistencija, 2015)
This article introduces some of the events, phenomena and facts of the Sovietisation (Bolshevization) of schools in annexed Lithuania in 1940–1941. The use of teachers in introducing the Bolshevik ideology to the society and pupils, the pseudo-elections to the Supreme Soviet of the USSR on 12 January 1941, the propaganda campaign for adult education, and other aspects of the research that have been examined or have just been brought up (including the aspect of adaptation to the occupants, cooperation with them, and resistance, which will be developed more in the final part of the research), are mainly illustrated by the examples of the archival documents that reflect the situation in the Šakiai County. An address to teachers of 19 November 1940 and fragments of other documents are published.
Keywords: soviet occupation; soviet education; communist indoctrination; resistance; collaboration